Efektivitas E-Modul Sistem Pencernaan Berbasis Problem Solving Terhadap Kemampuan Pemecahan Masalah - Irvan Permana*; Zulhijatiningsih Zulhijatiningsih; Surti Kurniasih (Universitas Syiah Kuala, 2021)
Learning during the Covid-19 pandemic has largely shifted to online learning. In response to this, it is necessary to prepare teaching materials that support online learning, one of which is the use of electronic models or e-modules. This is a development research with referring design to the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) which aims to produce electronic modules on science subjects with digestive system material as teaching materials for VIII grade junior high school students to enhance problem solving skill. ADDIE development design includes identification of potentials and problems, data collection, product design, design validation, design revision, limited-scale product trials, product revisions, wide-scale use trials and final products. The resulting e-module is declared feasible based on validation by material and media experts and very feasible by linguists. The results of the limited and wide-scale trial showed very good interpretation based on student responses. acquisition of an average N-Gain score of 0,57 and categorized as moderate. The pretest and posttest scores obtained by students were 37,35 and 73,53 respectively. If viewed from the school KKM score of ≥70 then the average posttest score obtained is complete. The results showed that the electronic module in science subjects with digestive system material met the requirements and was suitable for use as teaching materials for grade VIII students of SMPIT Kaifa Bogor.